Acoustic Week in Canada 2020 Sherbrooke Conference Announcement - Robin, Olivier (Canadian Acoustics, 2019)
Acoustics Week in Canada 2020 will be held on October 7-9, in Sherbrooke, Québec. You are invited to be part of this three-day conference featuring the latest developments in Canadian acoustics and vibration. Sherbrooke is well known in acoustics for the Groupe d’Acoustique de l’Université de Sherbrooke (GAUS) founded in 1984. The conference will be an excellent opportunity to visit or rediscover the GAUS during the International Year of Sound!